2019
DOI: 10.1002/1873-3468.13471
|View full text |Cite
|
Sign up to set email alerts
|

Cryo‐EM structure of the MinCD copolymeric filament from Pseudomonas aeruginosa at 3.1 Å resolution

Abstract: Positioning of the division site in many bacterial species relies on the MinCDE system, which prevents the cytokinetic Z‐ring from assembling anywhere but the mid‐cell, through an oscillatory diffusion‐reaction mechanism. MinD dimers bind to membranes and, via their partner MinC, inhibit the polymerization of cell division protein FtsZ into the Z‐ring. MinC and MinD form polymeric assemblies in solution and on cell membranes. Here, we report the high‐resolution cryo‐EM structure of the copolymeric filaments of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…MinD forms a dimer, structurally similar to ParA, but does not bind to DNA. Nonetheless, it was recently shown that MinD forms filaments, in the presence of its interacting partner MinC 53 . However, comparison of the MinCD filament to our cryo-EM structure of the ParA2 vc -ATPγS-DNA filament (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…MinD forms a dimer, structurally similar to ParA, but does not bind to DNA. Nonetheless, it was recently shown that MinD forms filaments, in the presence of its interacting partner MinC 53 . However, comparison of the MinCD filament to our cryo-EM structure of the ParA2 vc -ATPγS-DNA filament (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…MinC and MinD from E. coli, Pseudomonas aeruginosa , and A. aeolicus readily form copolymers in the presence of ATP composed of alternating dimers ( 13 , 14 , 15 , 16 ). ClpXP is known to disassemble FtsZ polymers in vitro ( 4 , 20 ); therefore, we tested if ClpXP could also prevent assembly of alternating MinCD copolymers or destabilize them after they assemble.…”
Section: Resultsmentioning
confidence: 99%
“…MinC and MinD from several organisms, including E. coli , assemble into ATP-dependent cofilaments in vitro ( 13 , 14 , 15 , 16 ). The Lowe group solved a crystal structure of the Aquifex aeolicus MinCD complex, which supports a model in which A. aeolicus copolymers contain alternating MinC and MinD dimers ( 13 , 14 ).…”
mentioning
confidence: 99%
“…Significantly, ParAB proteins interact with various components of the MinCDE machinery, ParB interacts with MinE, and MinC is a partner of ParA. Pae MinCD proteins organize into filaments at the membranes apart from the midcell, and they may form the scaffold for other proteins to bind there ( 82 ). Interactions with Min proteins may facilitate positioning of ParB- ori complexes in the cells and/or coordinate the cell division process with chromosome segregation ( 3 ).…”
Section: Discussionmentioning
confidence: 99%